Integrating concentrated solar power with seawater desalination technologies: a multi-regional environmental assessment - Mohamed Alhaj (17151073) (2019)
Using renewable energy to power seawater desalination technologies can reduce the environmental impacts of a process which is essential for global water security. However, the uneven geospatial distribution of renewable energy resources and regions of water scarcity results in unequal environmental benefits which creates uncertainty for global policy making. Hence, this study explores the relation between renewable energy resources, freshwater demand, and associated environmental impacts of desalination plants driven by renewable energy at a global scale using a comparative life-cycle assessment approach. We focus on an optimized solar-driven thermal desalination plant that we developed which can be used in seawater and brackish water treatment. By examining the life-cycle impact of the proposed plant in seven water-stressed cities, we found that the mean value for CO2 emissions is 4.32 kg CO2 eq./m3 of desalted water which is 47% lower than conventional thermal desalination. There is a variation by as much as 80% and 95% in the climate change and water depletion, categories respectively across the selected cities. The multi-city analysis provides energy and water utilities, CSP project developers, and environmental authorities a global assessment of the environmental impact of solar desalination and sheds light on the correlation between solar intensity and seawater conditions on the overall environmental impact of this technology. Other Information Published in: Environmental Research Letters License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1088/1748-9326/ab1d74